TED—trazodone effectiveness in depression: a naturalistic study of the effeciveness of trazodone in extended release formulation compared to SSRIs in patients with a major depressive disorder - Dudek, Dominika; Chrobak, Adrian Andrzej; Krupa, Anna Julia; Gorostowicz, Aleksandra; Gerlich, Adrian; Juryk, Andrzej; Siwek, Marcin (Frontiers in Pharmacology, 2023)
Selective serotonin reuptake inhibitors (SSRIs) are the most often used medications to treat major depressive disorder (MDD). Despite their effectiveness in reducing depressive symptoms several issues are associated with their use in MDD such as limited improvement of anhedonia, emergence of emotional blunting, induction or exacerbation of insomnia and sexual dysfunction. Due to its unique pharmacodynamic profile, trazodone might not only be effective in MDD, but also devoid of the issues related to treatment noted with SSRIs. The aim of this 12-week non-inferiority naturalistic observation was to compare the effectiveness and tolerability of SSRIs and trazodone in extendedrelease (XR) in MDD. 186 subjects were recruited, 92 received trazodone XR and 94 SSRIs. Patients were allocated to trazodone XR or SSRIs according to attending physician based on clinical evaluation. Assessments at baseline and weeks 2, 4, 8, and 12 were conducted to evaluate the severity of depression (Montgomery-Åsberg Depression Rating Scale, clinician and patient rated Quick Inventory of Depressive Symptomatology -the primary endpoints of the study), anhedonia (Snaith-Hamilton Pleasure Scale), anxiety (Hamilton Anxiety Rating Scale), insomnia (Athens Insomnia Scale) and therapeutic efficacy (Clinical Global Impression Scale). After 12 weeks, trazodone XR was more effective than SSRIs in reducing the severity of depression, anxiety, insomnia. There was a trend for higher effectiveness of trazodone XR vs. SSRIs which became insignificant after controlling the results for the duration of previous psychiatric treatment as a covariate. The proportion of treatment responsive subjects in trazodone XR group compared to SSRIs was comparable or higher. The proportion of patients achieving remission was higher in the trazodone XR arm vs. SSRIs arm. In sum, the results indicate that trazodone XR is effective in MDD in the "real-world" setting. It's potential superiority over SSRIs in addressing particular symptomatic dimensions should be verified in future studies.